2020
DOI: 10.3389/fmicb.2020.00378
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of Various Chaperon-Usher Fimbriae, Curli Fimbriae, and Type 4 Pili of Enterohemorrhagic Escherichia coli O157:H7 Sakai

Abstract: Enterohemorrhagic Escherichia coli (EHEC) is a highly pathogenic strain leading to hemorrhagic colitis and to the hemolytic-uremic syndrome (HUS) in humans. The mechanisms by which pathogenic E. coli infect and colonize humans leading to the typical disease pattern are in focus of many investigations. The adhesion of EHEC to epithelial cells by the coordinated translocation of receptor Tir and surface expression of corresponding adhesin intimin is a key event in host-pathogen-interaction. However, less is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The initial contact of E. coli O157:H7 with enterocytes involves nonintimin adhesion factors acting in accordance with temporal suppression of flagella expression. Curli fimbriae-associated amyloid fibers, assembled on the bacterial surface, congribute to E. coli O157:H7 biofilm formation and attachment to both human and bovine cells [48][49][50][51]. Curli expression and motility are conversely regulated by the PchE transcriptional factor.…”
Section: Adherence To Host Cellsmentioning
confidence: 99%
“…The initial contact of E. coli O157:H7 with enterocytes involves nonintimin adhesion factors acting in accordance with temporal suppression of flagella expression. Curli fimbriae-associated amyloid fibers, assembled on the bacterial surface, congribute to E. coli O157:H7 biofilm formation and attachment to both human and bovine cells [48][49][50][51]. Curli expression and motility are conversely regulated by the PchE transcriptional factor.…”
Section: Adherence To Host Cellsmentioning
confidence: 99%
“…In bacteria, a large variety of adhesive filaments have been well studied. These include chaperone-usher (CU), curli, type-IV (T4P) and type-V pili (T5P) in Gram-negative bacteria, and sortase-dependent pili in Gram-positive bacteria [5][6][7][8][9][10][11] .In archaea, cell adhesion and biofilm formation are far less understood. So far, the best studied archaeal adhesive filaments are of the type-IV pilus superfamily (T4FF) [12][13][14][15] .…”
mentioning
confidence: 99%
“…In bacteria, a large variety of adhesive filaments have been well studied. These include chaperone-usher (CU), curli, type-IV (T4P) and type-V pili (T5P) in Gram-negative bacteria, and sortase-dependent pili in Gram-positive bacteria [5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Several prior experiments demonstrated that type 1 fimbriae were implicated in autoagglutination and binding. For instance, expressions of the type 1 fimbriae, Curli and FimH, lead to autoagglutination in Escherichia coli 13 15 . Farfan et al (2011) found that Lpf fimbriae binds the extracellular matrix (ECM) proteins of the host cell.…”
Section: Discussionmentioning
confidence: 99%